Implications of seed policies for on-farm agro-biodiversity in Ethiopia and Uganda - Otieno, G.A.; Reynolds, Travis W.; Karasapan, A.; López Noriega, Isabel (Canadian Center of Science and Education, 2017)
Across East Africa, national seed policies and commercial seed enterprises have focused on increasing farmers’ access to modern seed varieties. These new varieties are developed and delivered to farmers via the formal seed system, which is comprised of government and private sector seed breeders, processors, and vendors. However, the formal seed system only provides a small share (<20%) of smallholders’ seed in the region. Most farmers source seed from informal seed systems, including own-saved seed, exchanges with neighbors, and local seed markets. At the local level, informal seed systems are preferred by farmers because of proximity and local varietal preferences (e.g., crop variety tastes and suitability for local environmental conditions). At the national and regional levels, the conservation and use of local crop varieties through informal systems has also provided a wealth of crop genetic diversity increasingly recognized as critical for climate change adaptation. To evaluate how policies in East Africa impact seed systems we systematically code 117 provisions in 21 national seed policies in Ethiopia (n=11) and Uganda (n=10), highlighting the implications of current and proposed policies for the availability and accessibility of: (i) improved seed; (ii) quality-controlled seed; and (iii) genetically diverse local seed in both the formal and informal seed systems in each country.